CHILD’S HABITUAL RESIDENCE IN THE JURISPRUDENCE OF THE COURT OF JUSTICE OF THE EUROPEAN UNION - Stanivuković, Maja (Zbornik radova Pravnog fakulteta u Novom Sadu, 2022)
This article examines decisions of the Court of Justice of the European Union interpreting the concept of child’s habitual residence. The study of those decisions is essential for proper understanding of this key concept which appears in the Hague Convention on the Civil Aspects of International Child Abduction, the Convention on Jurisdiction, Applicable Law, Recognition, Enforcement and Co-operation in respect of Parental Responsibility and Measures for the Protection of Children, Protocol on the Law Applicable to Maintenance Obligations, Convention on the International Recovery of Child Support and Other Forms of Family Maintenance and the Convention on Protection of Children and Co-operation in Respect of Intercountry Adoption. Correct determination of the child’s habitual residence is a precondition for the correct and uniform application of these instruments which are all in force in Serbia. Since 2007, the Court has been asked on numerous occasions to provide answers to questions that were raised regarding the interpretation of habitual residence. Out of this rich practice, four judgments have been selected for presentation and analysis (Case A, Case Mercredi, Case C v M and Case HR).The practice of the Court of Justice focuses on the circumstances that need to be taken into account by the judge in case the parties are in dispute about the child’s habitual residence and on the guiding principles for assessing the relative value of these circumstances. Although the Court interprets the terms of Brussels II bis, those decisions have had significant and unifying impact on the interpretation of the Hague Child Protection Conventions, not only in the member states of the Union but also in other member states of the Hague conventions. The Court’s views have influenced the practice of the highest courts in Australia, Canada, UK and USA. It will therefore be of benefit to judges in Serbia to get acquainted with them and understand them, which is the main purpose of this article.